ANALYSIS OF COMPOSITE BIOMASS FUELS PROPERTIES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
There is a growing interest about the possibility of exploiting the local biomass as an energy source. The main resource for biofuel production in Latvia is wood. Water plants, like common reed, growing in nearly all of the water reservoirs in Latvia, and all cultivate plants and residues of cereal crops, also can be good alternative for solid bio fuels production. The aim of this paper is to analyze possibilities to make composite fuels from these recourses. The study reveals research of ash content and highest burning heat value in different composite biomass fuels. It contains analysis of samples obtained from various local Latvian biomass types, i.e. reed, wood, flax spray, hay, hemp and peat, by combining them in different proportions. The study contains optimal combining proportions of different biomass types for composite fuel production basing on the ash content and burning heat in them. The results of the study show that the value of wood highest burning heat is higher than another biomass types like reed, peat, hay, hemp and flax spray. It means that combining of different biomass types with wood, will reduce the calorific value of composite biomass. Also, wood is a fuel with a low ash content, and admixture of various biomass types available in Latvia, as well as admixture of coal dust to the wood in composite duels, increases ash content in the respective fuels. In order to increase the burning heat and decrease ash content value to the optimal level and to diversify raw materials necessary for biomass fuel generating process, the authors analyze possibilities of using composite fuels by combining wood and coal dust.